Reduced plasma levels of GM-CSF is a common feature of Schistosoma mansoni-infected school-aged children - Kamdem, Severin Donald; Kamguia, Leonel Meyo; Oumarou, Alim; Bitye, Bernard Marie Zambo; Lennard, Katie; Brombacher, Frank; Spangenberg, Thomas; Demarta-Gatsi, Claudia; Nono, Justin Komguep (Frontiers in Immunology, 2025)
BackgroundCurrently available schistosomiasis diagnostic and monitoring tools are limited, and the development of novel technologies is necessary to enhance disease diagnostic and surveillance by supporting elimination efforts. Novel disease-specific biomarkers can facilitate the development of these technologies. Through the comparison of parasite burden and host factors, we assessed whether host plasma cytokines could be used as robust biomarkers for intestinal schistosomiasis and associated pathology in school-aged children (SAC) living in endemic areas.MethodsLevels of host plasma cytokines were measured in SAC from a low-to-moderate burden region five months deworming with praziquantel, using Luminex assay for exploration analysis and ELISA for validation.ResultsThe concentration of GM-CSF, IL-2, and VEGF in plasma was significantly lower in schistosome-infected compared to non-infected children, as determined by Luminex assay. Further evaluation by ELISA revealed a negative correlation between GM-CSF plasma levels, but not those of IL-2 or VEGF, and S. mansoni egg burdens in infected individuals. Common coinfections in the study area such as geohelminths, hepatitis or malaria failed to alter plasma GM-CSF levels arguing in favor of a potential specific effect of S. mansoni infection on this cytokine. Receiver operating characteristic analysis confirmed GM-CSF as an acceptable predictive marker of S. mansoni infection, with an area under the curve (AUC) of 75%. Finally, the adjunct use of plasmatic GM-CSF thresholds for screening S. mansoni at-risk children and identify S. mansoni-infected ones increased the sensitivity of a single Kato-Katz test by averagely 15%.ConclusionsOur findings highlight the potential of using plasma GM-CSF levels to biomark S. mansoni infection and improve the sensitivity of single Kato-Katz based diagnostic for low- to-moderate burden infections.